Qualitative Study of Bioactive Components of Dill (Anethum graveolens L.) From Northern Morocco - Saloua Kerrouri; L.A. Lrhorfi; Sammama Amal; Elyahyaou Ouafae; Ould abdellahi Lella; Bouabid Bahia; Bengueddour Rachid (European Scientific Journal, ESJ, 2016)
This work aims to extract and identify bioactive molecules of the plant Anethum graveolens, commonly known as Dill, which occupies an important place in Moroccan vegetation. In order to optimise their later use in the field of herbal medicine and nutrition, a focus on the phytochemical analysis of an extract from different parts of the plant were examined by using preliminary tests and staining reaction precipitation by the use of specific reagents, or by thin layer chromatographic analysis (TLC). Phytochemical tests, different organs, aerial and underground part (on different areas of the plant), revealed the richness of this plants tannins, reducing compounds, alkaloids, coumarins, terpenoids, sterols, flavonoids, irridoides, and this screening has allowed us to show that for the extraction of polyphenols, methanol is the best extraction solvent.